2016
DOI: 10.1515/pjct-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous biological graphene based formulations for ink-jet printing

Abstract: The aim of the study was to produce heterophasic graphene nanoplatelets based formulation designed for ink-jet printing and biomedical applications. The compositions should meet two conditions: should be cytocompatible and have the rheological properties that allow to apply it with ink-jet printing technique. In view of the above conditions, the selection of suspensions components, such as binder, solvent and surfactants was performed. In the fi rst stage of the research the homogeneity of the dispersion of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Taking into account the cytocompatibility of the AKM-0531 surfactant (D2), confirmed in our previous work [ 25 ], the inks made with it can successfully be used in the cell cultures. The examination of the coatings’ micro- and macro-geometry showed no significant variances for coatings made with inks containing more than 5% of surfactant.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Taking into account the cytocompatibility of the AKM-0531 surfactant (D2), confirmed in our previous work [ 25 ], the inks made with it can successfully be used in the cell cultures. The examination of the coatings’ micro- and macro-geometry showed no significant variances for coatings made with inks containing more than 5% of surfactant.…”
Section: Resultsmentioning
confidence: 73%
“…Concentrations of the surfactant with respect to the whole ink solution are presented in Table 4 below. Previous studies have shown that the layers produced with the developed inks have not caused toxic effects against cells [25]; thus, it seems certain that the layers used in the current work are cytocompatible. The layers were printed on two different substrates: a 25-µm-thick flexible Kapton film (DuPont, Inc.; Wilmington, DE, USA) and the polystyrene cell culture plates from Nest Scientific Biotechnology (Wuxi Nest Scientific Co., Ltd.; Wuxi, Jiangsu, China).…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations